Cellulose Acetate Sulfate as a Lyotropic Liquid Crystalline Polyelectrolyte: Synthesis, Properties, and Application - D. D. Grinshpan; T. A. Savitskaya; N. G. Tsygankova; S. E. Makarevich; S. M. Tretsiakova; T. N. Nevar (International Journal of Polymer Science)
The optimal conditions of cellulose acetate sulfate (CAS) homogeneous synthesis with the yield of 94–98 wt.% have been determined. CAS was confirmed to have an even distribution of functional groups along the polymer chain. The polymer was characterized by an exceptionally high water solubility (up to 70 wt.%). The isothermal diagrams of its solubility in water-alcohol media have been obtained. CAS aqueous solutions stability, electrolytic, thermal, and viscous properties have been defined. The main hydrodynamic characteristics such as intrinsic viscosity, Huggins constant, and crossover concentration have been evaluated. The parameters of polymer chain thermodynamic rigidity have been calculated. The formation of liquid crystalline structures in concentrated CAS solutions has been confirmed. CAS was recommended to be used as a binder for the medicinal forms of activated carbon and carbon sorbent for water treatment, hydrophilic ointment foundation.